The Relationship Between Vocabulary Mastery and English Reading Skills in English Study Program Students at Ummat - Hasmawati, Siti Ayuni; Ilham, Ilham; Ariyani, Etika (Journal of English Language and Education, 2025)
This study analyzes the correlation between knowledge mastery and English reading ability in 17 English Education students of Muhammadiyah University of Mataram. The correlational quantitative method was applied with comprehension test and reading test instruments, then analyzed using the Pearson test. The results showed a very strong correlation of 0.905 (p 0.001), indicating that increasing comprehension mastery is closely related to increasing reading ability. This finding emphasizes the importance of emphasizing learning in an effort to improve understanding of English academic texts.